Upgrading Kemampuan Pembukuan Sederhana dan Penggunaan Aplikasi (Microsoft Office) bagi Perangkat Desa: Upgrading Simple Bookkeeping Skills and Application Use (Microsoft Office) for Village Apparatus - Novi Caroko; Lilis Kurniasari; Novi Diah Wulandari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Based Village Law No. 6 of 2014 states legitimacy for village apparatus to organize a government in the village. The quality and quantity of human resources (HR) determine the success rate of government management and programs. The condition of village apparatus that show a low level of professionalism both in creativity, innovation, institutional management becomes a serious problem. The quality of village apparatus human resources that are currently reflected in the services produced in the pandemic era is quite declining, especially the entry of technology systems that require village apparatus to change the service system from manual to system with technology (computer). Such as simple bookkeeping that becomes the main point of recording and reporting every village activity. This community service program aims to provide training and assistance in upgrading simple bookkeeping skills and application use (Ms. Office) in Gembol village. The method of the community service program in the form of assistance to Gembol village devices is by preparing, licensing, socialization of activities, surveys, observation, and mentoring in the form of education, training, and measurement of results. Community service in Gembol village has been carried out successfully. The evaluation results showed the interest of village apparatus in improving the quality of human resources through mentoring and training sustainably. The improvement in training results can be seen from the evaluation that shows the low understanding of village apparatus for simple bookkeeping by Law No. 6 of 2014.